Hydraulic Parameters for the Euphrates Aquifer in the Southern Part of Haditha district, Al-Anbar Governorate - AL-Dulaimi, Ali M.; Al- Shammaa, Ayser M. (Iraqi Journal of Science, 2023)
One of the primary goals of any study involving groundwater is to make an exact assessment of the physical properties of the layers containing the water. One of the most fruitful ways to approach this goal is to conduct a pumping test for the aquifer. To make the most use of groundwater in terms of sustainable water management, this study attempts to assess its hydraulic features relative to the most significant aquifer represented in the Euphrates formation. A pumping test was carried out on 6 wells where each well is accompanied by an observation well. Cooper-Jacob and Theis Recovery methods were used to determine the aquifer transmissivity and storage coefficient. The ranges for permeability, transmissivity, and specific yield are (0.42 - 3.05 m/day, 13.89 -76.47 m2/ day, and 0.018 - 0.036) respectively, whereas, calculated transmissivities based on specific capacity showed a wide range from 30.85 m2/day to 120.96 m2/day. This wide range reflects the complex lithology of the aquifer, which was influenced by structural elements including stress and joint density.